Análisis del clima organizacional y su incidencia en el desempeño laboral de los servidores públicos del GAD municipal Quinindé 2020 - Gallardo Andrade, Melody Maribel (2022)
This research was developed in the Quinindé municipal GAD and its main objective was to analyze the organizational climate and its impact on the work performance of public servants, work that began with the first objective; the exploration of the legal framework of the organizational climate and work performance through bibliographic and descriptive research to know the legal provisions that support the organizational climate and work performance of public servants in Ecuador. The field investigation was also applied through the interview with the mayor and the director of the Department of Human Talent of the Quinindé municipal GAD, followed by the survey of the 280 public servants governed by the LOSEP, which made it possible to collect and tabulate precise information on the current situation of the institution. Likewise, the deductive, inductive, analytical-synthetic and statistical methods were used, which allowed the decomposition and analysis of the object of study. As objective three; An improvement plan was designed that contributes to strengthening the organizational climate and work performance of the public servants of the Quinindé municipal GAD. With the application of these objectives, it was concluded that, in effect, there are laws that support public servants within their functions and that factors such as ignorance of the term organizational climate, motivation, leadership, training, and job performance evaluation affect employees. workers within the entity, in turn, through the application of the 5W+H1 tool, an improvement plan was proposed with strategies to strengthen the variables detected.